Legal Certainty in the Registration of Land Subject to the Hak Ulayat of Customary Law Communities Following ATR/BPN Ministerial Regulation No. 14 of 2024 - Muslim Lobubun (Jurnal Ilmu Hukum Kyadiren, 2025)
This study analyzes the legal certainty of registering land subject to the hak ulayat of customary law communities following the enactment of Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 14 of 2024. It employs normative legal research using statutory and conceptual approaches. The primary legal materials consist of legislation and judicial decisions, while the secondary legal materials comprise relevant literature and research findings. The study finds that ATR/BPN Ministerial Regulation No. 14 of 2024 establishes a multi-tiered framework for the administration and registration of Tanah Ulayat through inventory and identification, surveying and mapping, recording in the Daftar Tanah Ulayat (Customary Land Register), and optional registration as Hak Pengelolaan (Right of Management) for a Kesatuan Masyarakat Hukum Adat or as Hak Milik (Right of Ownership) over collectively held land for a Kelompok Anggota Masyarakat Hukum Adat. This framework strengthens legal certainty regarding the legal subject, land object, procedures, and legal consequences of registration. However, such certainty remains affected by the formal recognition of customary law communities, potential overlapping claims to land, and communities’ access to land administration. The study concludes that legal certainty concerning Tanah Ulayat must integrate administrative and substantive legal certainty so that registration does not diminish the communal character of customary tenure, the authority of customary institutions, or the continuing applicability of customary law.